Botriomicosis Cutánea. Un caso infantil y uno adulto (Journal on studies and research of academic knowledge, 2010)
Botryomycosis is a bacterial infection and Staphylococus aureus is its most common etiological agent it can involve cutaneous or internal organs with nodules, abscesses or fistulae, with a chronic, recurring course and a typical poor response to treatment even with prolonged antibiotic courses. We report 2 cases caused by S. aureus in a 38 year-old female and in a 13 year-old boy; both with excellent response to treatment.
Keywords: botrymycosis; granulomatous infection; grains; bacterial pseudamycosis